Implementasi Pembelajaran Akhlak dalam Menanamkan Kedisiplinan Tata Tertib Sekolah Siswa Kelas Atas MI Ahmad Maryam Surakarta Tahun 2016/ 2017 - , Supatmo; , Drs. Saring Marsudi, SH. M.Pd (2017)
Background this is the State of research aspects influenced MI Ahmad Maryam Surakarta showed that discipline in the students obey school code of conduct should be improved. So this research aims to study the implementation of mendiskripsikan in morals instilled discipline code of conduct school grade up MI Ahmad Maryam Surakarta 2016/2017 Years. This research is a kind of kualitatatif research, using design research Phenomenology. Data collection techniques used are interviews, observation and documentation. Technique of data analysis in this study i.e., include the reduction of the data, the presentation of data, and the withdrawal of the conclusion. The results of this research show that the implementation of learning attitudes of students in MI Ahmad Maryam Surakarta 2016/2017 year using the approach and strategy of the example application is done directly in the process of learning of morals. As for the strategies used to instill discipline the school code of conduct that is making the code of conduct of the school. Implementation of learning attitudes in instilling discipline discipline in students school MI Ahmad Maryam Surakarta 2016/2017 years contributed greatly to the consciousness of the students comply with the code of conduct. Keywords: Ethics, Discipline, Learning, The School's Code Of Conduct.